2014
DOI: 10.1007/s11356-014-3240-x
|View full text |Cite
|
Sign up to set email alerts
|

Can ornamental potted plants remove volatile organic compounds from indoor air? — a review

Abstract: Volatile organic compounds (VOCs) are found in indoor air, and many of these can affect human health (e.g. formaldehyde and benzene are carcinogenic). Plants affect the levels of VOCs in indoor environments, thus they represent a potential green solution for improving indoor air quality that at the same time can improve human health. This article reviews scientific studies of plants' ability to remove VOCs from indoor air. The focus of the review is on pathways of VOC removal by the plants and factors affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(47 citation statements)
references
References 107 publications
(222 reference statements)
0
42
2
3
Order By: Relevance
“…As plants are a source of VOCs, when selecting them for phytoremediation use the net effect must be considered. The Dela Cruz et al [58] review is an example where over a hundred indoor plant species were reviewed for their net removal capacities.…”
Section: Improving Air Qualitymentioning
confidence: 99%
“…As plants are a source of VOCs, when selecting them for phytoremediation use the net effect must be considered. The Dela Cruz et al [58] review is an example where over a hundred indoor plant species were reviewed for their net removal capacities.…”
Section: Improving Air Qualitymentioning
confidence: 99%
“…Foliage plants are those with attractive foliage and/or flowers that are able to survive and grow indoors (Chen et al, 2005 ). Results showed that foliage plants removed nearly 87% of air pollutants from sealed chambers within 24 h (Wolverton et al, 1984 , 1989 ; Cruz et al, 2014a ). For example, each plant of peace lily ( Spathiphyllum spp.…”
Section: Roles Of Leaves and Phyllosphere Microbes In Air Remediationmentioning
confidence: 99%
“…Active green walls are a green technology that can simultaneously treat a large number of air pollutants at a relatively low cost. This technology builds upon the vast literature purporting the air phytoremediation potential of potted plants ( [24,[26][27][28], plus references therein). Whilst pollutant reduction by potted plants has been well described, for in situ use, such systems will be severely limited in their efficacy [29].…”
Section: Introductionmentioning
confidence: 99%